Pengaruh Ukuran Pupa Beberapa Penggerek Batang Tebu terhadap Jumlah Populasi Tetrastichus sp. (Hymenoptera : Eulophidae) di Laboratorium - Julian Simatupang; Syahrial Oemry; Fatimah Zahara (Universitas Sumatera Utara, 2015)
The objective of this research was to study the effect of some pupae size of sugarcane stem boreron the Tetrastichus sp. population in laboratory. Complete randomized complete design with twofactors, i.e Tetrastichus sp. population ( 4, 5, and 6 pair ), and PBR, PBB, and PBK pupae size(pupae size of PBR : 2-2.9 cm, 3-3.4 cm and ≥ 3.5 cm, pupae size of PBB : 0.5-0.9 cm, 1-1.4 cmand ≥ 1.5 cm, pupae size of PBK : 0.5-0.9 cm, 1-1.4 cm and ≥ 1.5 cm) and three replications wasused to conducting this research at Laboratory of Sugarcane Research and Development SeiSemayang, Binjai, Medan, North of Sumatera from February until July 2013. The results showedthat pupae size of PBR, PBB and PBK significantly affected the number of emerging parasitoidadult and sex ratio. The highest number of parasitoid adult (19.84 adult) was founded at pupae sizeof PBR ≥ 3.5 cm treatment, meanwhile the lowest (0.94 adult) was founded at pupae size of PBK0.5-0.9 cm treatment. Sex ratio of male and female was 1 : 3.08.Keywords : Parasitoid, Sugarcane stem borer, Tetrastichus sp.